2016
DOI: 10.1039/c6tc00260a
|View full text |Cite
|
Sign up to set email alerts
|

Silver-induced reconstruction of an adeninate-based metal–organic framework for encapsulation of luminescent adenine-stabilized silver clusters

Abstract: Luminescent adenine-stabilized silver clusters were created by transforming adeninate bio-MOF-1 to MOF-69A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 95 publications
1
21
1
Order By: Relevance
“…Many frameworks are luminescent and through the combined engineering of inorganic nodes, organic linkers and guest space and therefore offer more design parameters than alternative materials in this area. Examples of approaches to tune the emission color include fine-tuning the linker 91,94,117 or the metal ion 118 (especially lanthanide ions 119 ) alone or in combination, or alternatively, by infiltrating the pores with luminescent species 120,121 or by creating MOF nanoparticles. 122 These materials are primarily targeted for use as phosphors that down-convert the emission of UV or blue LEDs to longer wavelengths and create broad spectrum white light emission.…”
Section: Energy Harvesting and Emissionmentioning
confidence: 99%
“…Many frameworks are luminescent and through the combined engineering of inorganic nodes, organic linkers and guest space and therefore offer more design parameters than alternative materials in this area. Examples of approaches to tune the emission color include fine-tuning the linker 91,94,117 or the metal ion 118 (especially lanthanide ions 119 ) alone or in combination, or alternatively, by infiltrating the pores with luminescent species 120,121 or by creating MOF nanoparticles. 122 These materials are primarily targeted for use as phosphors that down-convert the emission of UV or blue LEDs to longer wavelengths and create broad spectrum white light emission.…”
Section: Energy Harvesting and Emissionmentioning
confidence: 99%
“…13,14 To achieve high sensitivity and selectivity, ZIF-8 was also used as the host of optical sensing materials for trace detection. 15,16 The guests including GaN quantum dots, 17 Au nanoclusters, 18 Ag nanoclusters, 19 and silicon dioxide 20 was introduced into ZIF-8. For example, a BPEI-CQDs/ZIF-8 composite was reported that Cu 2+ is not only selectively enriched by ZIF-8 but also specically recognized by the carbon quantum dots of BPEI-CQDs.…”
Section: Introductionmentioning
confidence: 99%
“…Another factor that helps forming larger structures in these compounds is the presence of multi binding sites in their structures [3] which increase the prone of these materials to self-assemble and produce structures of one dimension (1D), two dimensions (2D), and three dimensions (3D). Nucleobases and nucleosides showed attractive attention due to multifunctional properties of these structures such as conductivity [4], magnetism [5, 6], luminescence [7, 8], drug delivery, bioactivity, porosity [9], gas sensor, and nanotechnology [10]. Guanosine nucleoside has shown the ability to form G-quartet by self-assembling via hydrogen bonding [11].…”
Section: Introductionmentioning
confidence: 99%